Limites da reforma agrária : lutas, memórias e experiências dos trabalhadores sem-terra : Assentamento Rio das Pedras - Uberlândia / MG - 1997-2006 - Medeiros, Edna Alves Pereira (2008)
The proposal of this work is to analyze the Brasilian agrarian question and, more specifically, the historical trajectory of the nesting Rio das Pedras, located in the city of Uberlândia, State of Minas Gerais. The central objective of this work consists of studying the social direction and politician of the agrarian reform in the city of Uberlândia, in the Triângulo Mineiro, having, as cloth of deep, the implemented governmental measures in relation to the agrarian reform, over all, from the years of 1960, in the perspective of the social fights stopped in the field, searching to understand the historical process in the Brazilian society that allowed the maintenance of the agrarian concentration, as well as the form with that the proposals officers had been the long one of the modified years being in you strike social. The related nesting is composed for 87 families and had its officialization legalized in October of 1997, moment where the Court of Court of appeals, in Belo Horizonte, suspended the Action of Repossession effected against the current Movement Land, Work and Freedom - MTL, carried through for Josias de Freitas, proprietor of the farm, allowing the permanence of the families in the place. During the period of encampment, the workers without land had lived deeply difficulties in the internal and external scope. Passed the period of encampment, the workers had continued in a situation of difficulties, mainly, happened of the scarcity of financial resources, of the assistance inexistence compatible technique with the necessities of the seated ones and the lack of organicidade of the seated families, in way that some families if see in an entangled complex, in its situation while small inserted agricultural producer in the market relations. However, these aspects, among others, had lead to the questioning in the way as the agrarian reform is being lead in the country, as well as of its necessity and viability. The arcabouço of this work counted on a specific bibliography and different sources of research on the agrarian question in Brazil. Documentary sources proceeding from the National Institute of Colonization and the Agrarian Reform-INCRA, the Pastoral Commission of Land-CPT, the Municipal City hall of Uberlândia-PMU, the Farming Censuses of Minas Gerais, divulged for the Brazilian Institute of Geography and Statistic-IBGE and the Movement Land, Work and Freedom-MTL, entity that organized the occupation of the farm Rio das Pedras, together to the workers without land; beyond interviews with the seated ones, photographs, the newspaper Correio of Uberlândia and magazines. The pressuposts of the theoric-metodologics had left of diverse references, not concentrating in specific theories.